Comparative analysis of methods for monitoring the condition of small cattle using modern technologies - Ginoyan, L. L.; Abraimov, N. T.; Sansyzbayev, B. S.; Kodabashyan, L. S.; Eranosyan, S. S.; Larin, D. R.; Khomyakov, A. A.; Pazylova, D.; Tileuberdi, A. (Brazilian journal of biology, 2024)
Abstract For successful animal husbandry, farmers need to monitor the health status of animals on a daily basis, as well as ensure the safety and protection of animals. In this regard, the problem of choosing the optimal system for monitoring the condition of farm animals in the modern market is urgent. The practical value of the scientific article is to analyze the problems of stakeholders and, based on the needs, conduct a comparative analysis of various modern systems for monitoring the condition of small cattle using the weighted sum method. The object of the study was the process of monitoring the condition of small cattle using RFID tags, as well as the ability to monitor their health depending on the chosen approach. The subject of the study was a livestock enterprise that raises small cattle. It was found that the health of small cattle directly affects the financial stability of the farm. In the presented study, the authors analyze the problems of stakeholders and, based on the needs of stakeholders, conduct a comparative analysis of various modern systems for monitoring the condition of small cattle using the weighted sum method. The results obtained will help farmers make informed decisions in the future when choosing the most appropriate monitoring option for more effective and high-quality monitoring of the condition of small cattle, thereby reducing the risk of diseases and increasing profits for companies. Resumo Para uma criação animal bem-sucedida, os agricultores têm de monitorizar diariamente o estado sanitário dos animais, bem como garantir a segurança e a protecção destes. A este respeito, o problema da escolha do sistema ótimo de controle do estado dos animais de criação no mercado moderno é urgente. O valor prático deste artigo científico é analisar os problemas das partes interessadas e, com base nas necessidades, realizar uma análise comparativa de vários sistemas modernos de monitoramento da condição de pequenos bovinos usando o método da soma ponderada. O objetivo deste estudo foi comparar os processos de monitoramento da condição de pequenos bovinos usando etiquetas RFID, bem como a capacidade de monitorar sua saúde, dependendo da abordagem escolhida. O assunto do estudo foi uma empresa pecuária que cria gado de pequeno porte. Verificou-se que a saúde dos pequenos bovinos afeta diretamente a estabilidade financeira da exploração. Os resultados obtidos ajudarão os agricultores, no futuro, a tomar decisões embasadas na informação, ao escolherem o sistema de controle mais adequado para uma monitorização mais eficaz e de alta qualidade da condição do gado de pequeno porte, reduzindo assim o risco de doenças e aumentando os lucros para as empresas.